Potensi Pengembangan Setigi sebagai Destinasi Wisata - Agung Yoga Asmoro; Muhyiddin Aziz (Universitas Islam Kadiri, 2020)
The new normal phase has already begun. The tourism sector is slowly starting to operate. Setigi (Selo Tirto Giri) is a new tourist destination in the Gresik Regency region that gets priority from the local government to operate. As a new tourist destination, Setigi should have the right development guide. This research was conducted with a qualitative approach for 1 (one) month, where we focused on aspects of qualitative data that refer to the criteria and indicators of tourism destination development. We collect data by field observations, in-depth interviews with key stakeholders, supported by quantitative non-reactive data. The analysis was carried out by the IFAS/EFAS analysis phase, followed by the SWOT/TOWS Matrix analysis technique. This research reveals that, in general, the management of Setigi is in harmony with the principles of the development of tourist destinations and tourist attractions. The manager has also strived to implement the Sapta Pesona criteria into the management of Setigi. However, there are some notes to improve Setigi's performance towards better tourism destinations.